Chapter Relazioni pericolose: i gesuati e la povertà - Lodone, Michele (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
This essay looks at the specific iconography of saint Jerome in the artistic commissions of the Jesuati during the 15th century. This specific iconography meant to show the Doctor of the Church as the illustrious founder of the congregation in place of Colombini who never was canonized and meant to presents their form of religious life and the rejection of the Holy Orders through the extremely rare illustration of the episode in the life of Saint Jerome: The anticiceroniano dream. The dissemination of this theme was previously attributed to Hieronymites of Fiesole.